Peran Religiusitas, Kepemimpinan Transformasional, Kepuasan Kerja dan Mediasi Organizational Citizenship Behavior terhadap Kinerja Guru - Dhaniel Hutagalung; Masduki Asbari; Miyv Fayzhall; Eny Ariyanto; Eva Agistiawati; Rachma Nadhila Sudiyono; Hatoli Waruwu; Francisca Sestri Goestjahjanti; Winanti Winanti; Teguh Yuwono (Universitas Muhammadiyah Enrekang, 2020)
This study aimed to measure the effect of religiosity, transformational leadership and job satisfaction on the teacher performance of private schools teachers in Tangerang which are mediated by organizational citizenship behavior. Data collection was done by simple random sampling via electronic to the private schools teacher population in Tangerang. The returned and valid questionnaire results were 224 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that religiosity, transformational leadership and job satisfaction have a positive and significant effect on the teacher performance, both directly and indirectly through mediating organizational citizenship behavior. Meanwhile, transformational leadership have not significant effect on the teacher performance directly without mediating organizational citizenship behavior. This new research proposed a model for building the teacher performance among the private school teachers in Tangerang through enhancing religiosity, transformational leadership and job satisfaction with organizational citizenship behavior as a mediator. This research could pave the way to improve teacher readiness in facing the era of education 4.0.